The Contribution of Islamic Religious Leaders to the Spiritual and Social Life of the Community in Ledong Timur Village - Namora Siregar, M. Tondi; Andi Surya, Maulana (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
This study aims to analyze the contribution of Islamic religious leaders in improving the spiritual and social life of the community in Ledong Timur Village, Aek Ledong District, Asahan Regency. The research employed a qualitative case study approach, using in-depth interviews, participant observation, and documentation. Twelve informants were selected through purposive sampling, including religious leaders, village officials, non-formal educators, and community members. Data were thematically analyzed through reduction, presentation, and conclusion drawing, and validated by triangulation and member-checking. The findings indicate that religious leaders play a crucial role in strengthening community spirituality through regular study sessions, worship guidance, and youth moral development. In the social sphere, they contribute through mutual cooperation, conflict mediation, and fundraising for the poor. These results highlight the role of religious leaders as educators, mediators, and social mobilizers who strengthen cohesion in rural communities.